The German enforceable notarial act in cross-border cases - Bormann, Jens (Lexonomica, 2022)
The subject of this article is to explain and discuss the legal framework for German enforceable notarial acts in cross-border traffic. The first part will illustrate the prerequisites for the enforcement of a notarial act in Germany, especially in circumstances when the creditor or debtor lives abroad. The second section is dedicated to the enforcement of German enforceable notarial acts abroad. After presenting the principles of international law, the main legislative acts regarding enforcement in the European and international framework will be analysed in detail.
Keywords: application for enforcement; clause; enforcement; enforcement certificate; enforcement order; exequatur procedure; notarial act; service